Happy thoughts: Mind wandering affects mood in daily life - Welz, Annett; Reinhard, Iris; Kühner, Christine (Mindfulness, 2018)
Mind wandering is often thought to have adverse consequences such as to deteriorate mood. However, more recent findings suggest that the effect of mind wandering on mood may depend on the specific thought contents that occur during mind-wandering episodes and may be influenced by trait-like interindividual differences. The current study examined prospective effects of mind wandering (MW) on mood in daily life as well as possible moderating effects of dispositional mindfulness and rumination. Forty-three university students aged 19 to 32 (61% women) filled out questionnaires on trait mindfulness and rumination. Subsequently, they underwent 5 days of electronic ambulatory assessment of MW and positive and negative affect in daily life ten times a day. Prospective models revealed positive effects of MW on mood, and negative affect was lowest when thoughts during MW were most pleasant. Although dispositional rumination and mindfulness significantly affected mood in daily life, no moderating effects of these traits were identified on the association between MW and mood. These results suggest that mind wandering is not a negative phenomenon per se but instead has adaptive consequences that can lead to mood improvements. Our findings highlight the importance of accounting for the thought content of mind-wandering episodes when investigating the functional outcomes of a wandering mind. Given that mind wandering frequently takes place in everyday life, interventions that encourage individuals to shift the content of their mind-wandering experiences towards pleasant topics may have an important impact particularly for clinical populations.